Manifestations of Sexuality of Children in the Environment of a Kindergarten - Rapošová, Petra (Kultura-Społeczeństwo-Edukacja, 2016)
This research project focuses on the presentation of sexuality in children before they enter the school system. The study provides theoretical basis of sexuality and sex education. Included in the research project are the result of the on site study with parents and children of the preschool and kindergarden age and also the teachers working with this target group. Results not only describe sexual presentation of the children but also the reactions of others to those presentations.